2019
DOI: 10.3390/cancers11091383
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Carbenoxolone Reduces Lung Metastases

Abstract: Carbenoxolone is an anti-inflammatory compound and a derivate of a natural substance from the licorice plant. We previously showed that carbenoxolone reduces the metastatic burden in the lungs of mice through its antagonistic effect on high mobility group box 1 (HMGB1). To further enhance carbenoxolone’s activity and localization in the lungs, thereby reducing the potential adverse side effects resulting from systemic exposure, we developed a poly(lactic-co-glycolic acid) (PLGA) slow-release system for pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Table 2 shows DLS analysis performed in a similar way to that previously reported [ 38 , 39 , 40 ]. The CI-vesicles had an average hydrodynamic diameter around 620.7 nm, which increased when PG-E was encapsulated in CI-vesicles (797.5 nm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows DLS analysis performed in a similar way to that previously reported [ 38 , 39 , 40 ]. The CI-vesicles had an average hydrodynamic diameter around 620.7 nm, which increased when PG-E was encapsulated in CI-vesicles (797.5 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic light scattering (DLS) was used to detect particle size, zeta potential, and polydispersity index at a temperature of 20 °C using a Zetasizer Nano (Malvern Instruments, Malvern, UK) in a similar way as previously was reported [ 38 , 39 , 40 ]. Transmission electron microscopy (TEM) was performed as described previously [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to one author, when treating gastrointestinal inflammation with carbenoxolone 4 , the common dosage is ‘100 mg for 1 week, three times a week, followed by a reduction to 50 mg every other day, to prevent potential side effects such as sodium retention, hypokalaemia, increased blood pressure and edema’. 78 …”
Section: Adverse Effectsmentioning
confidence: 99%
“…According to one author, when treating gastrointestinal inflammation with carbenoxolone 4, the common dosage is '100 mg for 1 week, three times a week, followed by a reduction to 50 mg every other day, to prevent potential side effects such as sodium retention, hypokalaemia, increased blood pressure and edema'. 78 Both GLA 1 and GRA 3 exhibit antithrombotic properties, inhibiting coagulation factor Xa and thrombin. A case of haemorrhagic stroke and cerebral microbleeds attributed to high intake of liquorice root supplement has been reported.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…1); it has anti-inflammatory, -viral, -tumor, -bacterial, -fibrosis properties and neuroprotective activities amongst other extensive pharmacological activities. [11][12][13][14][15][16] It has been reported that CBX administration decreased lung inflammation in rats with pulmonary hypertension by increasing an anti-inflammatory cytokine, IL-10; decreasing tumor necrosis factor (TNF)-α, IL-1β, IL-6 and monocyte infiltration; and reducing the number of CD3 + and CD4 + T cells in lung tissues. 11) Another study indicated that CBX significantly inhibits NLRP3 activation and proinflammatory cytokine production thereby alleviating renal function and pathological damage in sepsis-induced acute kidney injury.…”
Section: Introductionmentioning
confidence: 99%